Seasonal Impact in the Frequency of Intrahepatic Cholestasis of Pregnancy - Cem Yaşar Sanhal; Korkut Dağlar; Özgür Kara; Ayşe Kırbaş; Dilek Uygur; Aykan Yücel (Gynecology Obstetrics & Reproductive Medicine, 2016)
Objective: To evaluate the presence of any seasonal variation in the frequency of intrahepatic cholestasis of pregnancy (ICP). Study Design: A total of 126 cases with ICP were compared with a cohort of 37614 pregnant women who delivered. The diagnosis ICP was performed on the basis of severe itching and the absence of dermal rash and any other hepatic disease, with the co-existence of elevated serum aminotransferase levels and/or serum bile acid concentration. For each month and season, observed and expected ICP rates were analysed and compared by using chi-square statistics. Multivariate logistic regression was performed to investigate certain parameters on cumulative risk. Results: A significantly lower frequency of ICP in winter (6/126 (4.8%), p=0.001) and a significantly higher frequency in spring (44/126 (34.9%), p=0.034) were detected. A 2.1 and 3.8-fold higher risk were found for the nulliparity and the twin pregnancy, respectively. Logistic regression analysis confirmed the significant (10-fold) decrease in the frequency of ICP in winter. The significance of spring did not persist after the adjustment. Conclusion: Main outcome of the study points at seasonality in ICP frequency. Future studies in different populations may reveal data about factors that interact with seasonality and playing roles in ICP.